DINAMIKA SIKLUS HIDUP PERUSAHAAN, KEPEMILIKAN MANAJERIAL, DAN KEAHLIAN CHIEF FINANCIAL OFFICER TERHADAP MANAJEMEN LABA RIIL - Salva Yuniarti Putri; Dicky Jhoansyah; Tetty Sufianty Zafar (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The growth slowdown in Indonesia's manufacturing sector during the 2021-2024 period created significant operational pressures for companies to maintain financial performance. This condition triggered potential opportunistic actions by management through real earnings management practices to avoid negative market sentiment. This study aims to examine the effect of firm life cycle dynamics, managerial ownership, and Chief Financial Officer (CFO) expertise on real earnings management projected through abnormal operating cash flows. The research method applied is an explanatory quantitative approach with multiple linear regression analysis. The research sample includes 450 observations of manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2024 period, selected using purposive sampling, and processed with SPSS 25 software. The partial test results show that the firm life cycle in the maturity phase has a positive and significant effect on real earnings management due to high market expectations for earnings stability. Managerial ownership also exerts a positive and significant influence, indicating the emergence of an entrenchment effect where extensive authority loosens internal monitoring. CFO expertise is found not to affect real earnings management because real transaction manipulation decisions constitute a collective strategic policy of the entire board of directors. The simultaneous test proves that the firm life cycle, managerial ownership, and CFO expertise significantly affect real earnings management, with a contribution value of 21.9%.